Internet translation, censorship and homosexuality : translating brokeback mountain in Chinese communities - Liu, Qian (2017)
Chinese censorship on cultural products including translation has long been criticized as a violation of free speech and has refrained minority groups from gaining visibility and positive social perception. However, the situation is gradually changing with the emergence of Internet translation, which has emerged as a distinctive phenomenon that translation studies till now has yet fully described. This paper aims to examine the possibility of Internet translation as a means to circumvent the state censorship in China in the translation of sensitive topics such as homosexuality. Brokeback Mountain, as a famed representation of homosexuality and a clear example of censorship and self-censorship is used as a case study. Through comparing the mainland Chinese version and Internet version, it is argued that Internet translation does provide an ideal opportunity to bypass the omnipresent censorship mechanism in China. A further attempt was made to respond to the presumption that Internet translation equals low quality. After detailed comparison, it is argued that there is no proof showing that professional translation is superior than the Internet translation no matter in the ways of translator’s manipulation in the target text or in the overall translation quality in terms of accuracy. This study will rebound to the benefit of the society in that it will further justify and promote the development of Internet translation and thus to some extent salvage the situation of censorship in China. Key words: Censorship in China, Internet translation, Homosexuality, Translation quality